Pengaruh Variasi Media Pendingin Terhadap Kekerasan Hasil Las MIG Material ST 42 - Andreas Giovani Manik; Nyoman Arya Wigraha; Ida Bagus Putu Purwadnyana (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
ST 42 steel is a low carbon steel widely used in construction and manufacturing due to its good weldability and ductility; however, it has relatively low hardness. One of the factors affecting the hardness of welded joints is the cooling medium applied after the welding process. This study aims to analyze the effect of cooling media variations on the hardness of MIG (Metal Inert Gas) welded ST 42 steel. The research was conducted using an experimental method by performing MIG welding on ST 42 steel specimens, followed by rapid cooling (quenching) using three different cooling media, namely water, seawater, and oil. Hardness testing was carried out using the Vickers method to obtain hardness values for each welded specimen. The experimental data were analyzed using descriptive quantitative analysis by comparing the hardness values resulting from each cooling medium. The results show that variations in cooling media have a significant effect on the hardness of MIG welded ST 42 steel. Seawater cooling produced the highest hardness values, followed by water and oil cooling. The differences in hardness values are influenced by the different cooling rates of each medium. In conclusion, the selection of an appropriate cooling medium plays an important role in improving the hardness of MIG welded ST 42 steel.